A remote lecturing system offering complementary non-verbal information in lectures. (1st January 2013) - Kunimune, Hisayoshi; Niimura, Masaaki
This paper proposes a remote lecturing system which has some features to complement non-verbal information in lectures. The proposed system provides students entire sight of the teacher, the blackboard, lecture slides, and so on with low definition video. The students can get the high definition pictures of where they would like to watch by clipping a region on the video. They also can write notes directly on the clipped pictures. The system collects data of clipped regions and wrote notes from the students, and offers its users the data to complement non-verbal information in the lecture. The system also provides the teacher and the students the video of others' faces depending on the situations of the lecture. This paper also organises the verbal and non-verbal information in several situations in a lecture.